PENERAPAN IDENTITY AWARENESS TRAINING UNTUK PENINGKATAN REGULASI PADA ATLET REMAJA SENTRA LATIHAN OLAHRAGAWAN MUDA POTENSIAL UNIVERSITAS NEGERI SURABAYA - Rachman Widohardhono; Miftakhul Jannah; Wafiq Alfina Oktafiani; Andy Ledy Permata Putri; Nabila Rachman (Indonesian Collaboration Journal of Community Services (ICJCS), 2023)
The National Potential Young Athlete Training Center  is part of the Grand National Sports Design. Potential young athletes are at youth level and have a dual role as athletes and students. This dual role requires self-regulation abilities. Therefore, identity awareness training activities were held. This activity aims to increase self-regulation scores in teenage athletes who are members of SLOMPN UNESA. The results showed that 70.83% experienced an increase in scores after carrying out the activities. The identity awareness training mechanism makes athletes more familiar with what adolescence is like and the dual roles they play today. Other results regarding the implementation of activities are shown by the evaluation score for the implementation of activities which is very good at 83.33